The Exponential Attractors for the g-Navier-Stokes Equations - Delin Wu; Jicheng Tao (Journal of Function Spaces and Applications)
We consider the exponential attractors for the two-dimensional g-Navier-Stokes equations in bounded domain Ω. We establish the existence of the exponential attractor in L2(Ω).